Drug Induced Acute Pancreatitis - Spirovska, Tatjana; Seljmani, Redjep; Kuzmanovska, Biljana; Kartalov, Andrijan; Mikjunovikj, Ljubica; Andonovska, Biljana (SHMSHM - AAMD, 2016)
Acute pancreatitis is a severe disease with considerable morbidity and mortality. Drug-induced acute pancreatitis is rare, with an estimated incidence of 0.1-2%. More than 100 drugs have been implicated in causing the disease: acetaminophen has been associated with acute pancreatitis in cases where there has been an overdose of drugs; however, the frequency is rare. Based on analysis of the level of evidence, 4 classes of drugs could be identified. We report the case of a 28-year-old man who presented abdominal pain and elevated pancreatic enzymes suggesting acute pancreatitis, severe metabolic acidosis and systemic inflammatory response syndrome after overdosing on a drug containing acetaminophen. He was taking acetaminophen more than 5 g every day two weeks.Workup including an ultrasound,CT scan, microbiological and serological analysis failed to reveal any obvious etiology for the pancreatitis. The possibility of drug-induced pancreatitis was considered and acetaminophen was thought to be the probable etiologic agent and discontinued. A review of the relevant literature is also presented. Drug-induced acute pancreatitis is challenging for clinicians and a detailed mechanism is unknown. It is very important to rule out drug-induced pancreatitis when treating pancreatitis with an unknown etiology.
Акутен панкреатит индуциран од лек
Keywords: Case report; Drug induced; Acetaminophen; Acute pancreatitis